KOMPARASI PRESTASI BELAJAR MATEMATIKA BERDASARKAN GENDER DI MTs. MIFTAHUL IMAN NW BUNDUA TAHUN PELAJARAN 2024/2025 - Yunus, Muhamad (Journal of Social Science and Multidisciplinary Analysis, 2025)
The researcher wanted to determine whether there were differences in mathematics abilities between male and female students at MTs Miftahul Iman NW Bundua in the 2024/2025 academic year. Every study has a clear objective, and achieving this objective requires adequate preparation and careful planning. This includes conducting preliminary observations to facilitate data collection and collaboration with the school. The ex post pacto method was used in this study. The population comprised all students at MTs Miftahul Iman NW Bundua in the 2024/2025 academic year, with a sample size of 150 students from grades VII and VIII. Three data collection techniques were used: observation, interviews, and documentation, resulting in qualitative and quantitative data. Quantitative data were obtained through documentation and then analyzed. To determine data normality, a chi-square test was performed, yielding a value of 7.99 for male students and 3.69 for female students. Meanwhile, to test data homogeneity, the Bartlett formula was used, yielding a value of 0.647. Based on the results of the hypothesis test, it can be concluded that because the calculated t value = 1.648 is smaller than the t table value = 1.668, Ha is rejected and Ho is accepted. Therefore, it can be concluded that there is no significant difference in mathematics ability between male and female students at MTs Miftahul Iman NW Bundua in the 2024/2025 academic year.